Blockchain Adoption for Sustainable Supply Chain Management: Economic, Environmental, and Social Perspectives - Munir, M. Adeel; Habib, M. Salman; Hussain, Amjad; Shahbaz, Muhammad Ali; Qamar, Adnan; Masood, Tariq; Sultan, M.; Mujtaba, M. A.; Imran, Shahid; Hasan, Mudassir; Akhtar, Muhammad Saeed; Uzair Ayub, Hafiz Muhammad; et al. (Frontiers in Energy Research, 2022)
Due to rapid increase of environmental degradation and depletion of natural resources, the focus is shifted from economic to socio-environmental problems. Blockchain is a disruptive technology which has potential to restructure the entire supply chain for sustainable practices. Blockchain is a distributed ledger which provides a digital database for recording all the transactions among all actors of the supply chain. The main features of this nascent technology in supply chain management are traceability, reliability, transparency, and sustainability. The main purpose of this research is to explore the literature relevant to blockchain for sustainable supply chain management. The focus of this review is on the sustainability of the blockchain-based supply chain concerning environmental conservation, social equality, and governance effectiveness. Using a systematic literature review, total 125 papers are evaluated related to model or framework development, relevant case studies, and theoretical developments for blockchain integration in the supply chain in paradigm of sustainability. Different industrial sectors such as aviation, shipping, agriculture and food, manufacturing, automotive, pharmaceutical, and other multinational companies involved in the global supply chain are analysed. This study has highlighted relevant opportunities, environmental and social impacts, trends in the circular supply chain, current advanced technologies along with critical success factors and different challenges for their adoption and implementation in supply chain. Furthermore, research areas, gaps in the existing research, and future research directions are discussed. The findings of this study show that blockchain has the potential to bring a revolution in the performance of supply chain from the perspective of sustainability. The study will be helpful for the managers and practitioners to understand the procedure of blockchain adoption, and to increase the probability of its successful implementation for a sustainable supply chain.